Exploring English Teachers’ Strategies for Writing Instruction at MAN Palopo: A Qualitative Study - Alyesa Adelia Putri; Rustan Santaria; Jufriadi (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates English teachers’ strategies for teaching writing in an Indonesian Islamic senior high school context, with particular emphasis on identifying dominant and effective instructional approaches. Employing a qualitative descriptive design, the study was conducted at MAN Palopo and involved two experienced English teachers selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using John W. Creswell’s qualitative procedures, including data transcription, coding, categorization, and thematic interpretation. The findings reveal six key strategies implemented across different stages of writing instruction: Genre-Based Approach, Cooperative Learning, Quick Write, RAFT, Journalistic Questions (5W1H), and Blooming Sentences. Among these, the Genre-Based Approach and Cooperative Learning emerged as the most dominant due to their systematic scaffolding, alignment with curriculum requirements, and ability to promote student interaction and engagement. These strategies were effectively integrated across pre-writing, while-writing, and post-writing phases, contributing to improved student writing proficiency, increased confidence, and more active classroom participation. The study highlights that the integration of structured, collaborative, and context-sensitive strategies is essential for effective writing instruction in EFL classrooms. It also underscores the need for sustained professional development and institutional support to enable teachers to adapt and implement diverse pedagogical approaches. This research contributes to the growing body of literature on context-responsive writing pedagogy in Indonesian secondary education and offers practical implications for enhancing teaching practices in similar settings.